Клінічна характеристика позапечінкових проявів у хворих на хронічний гепатит С - Рябоконь, Юрій Юрійович; Ryabokon, Yu. Yu. (Запорізький державний медичний університет, 2011)
Наведено відомості сучасної наукової літератури щодо позапечінкових проявів хронічної HCV-інфекції та представлено дані власних досліджень спектра цих проявів у хворих на хронічний гепатит С. In the work modern literature data about extrahepatic manifestatins of chronic HCV-infection is cited and results of own researches of a spectrum of these manifestations in patients with chronic hepatitis C are presented.
Clinical characteristic of extrahepatic manifestations in patients with chronic hepatitis C
Keywords: chronic hepatitis C; extrahepatic manifestations